Corticotomy-assisted retraction: An outcome assessment - S Vijayashri Sakthi; B Vikraman; V R Shobana; S Kavitha Iyer; N R Krishnaswamy (Wolters Kluwer Medknow Publications, 2014)
Background: To assess the efficiency and treatment outcome of patients treated with corticotomy-assisted en-masse orthodontic retraction as compared with the en-masse retraction without corticotomy. Materials and Methods: Forty adult patients with bimaxillary protrusion requiring correction of bidental proclination constituted the sample. The study group consisted of 22 patients (male 11, female 11) willing to undergo surgery to reduce the duration of their orthodontic treatment and 18 patients (male 9, female 9) desirous of undergoing conventional orthodontic treatment without surgical intervention constituted the control group. Comparison of rate of retraction and anchor loss between the study and the control group was assessed. Results: Average rate of space closure of 1.8 mm/month in the maxilla and 1.57 mm/month in the mandible was observed in the study group compared to 1.02 mm/month in the maxilla and 0.87 mm/month in the mandible in the control group. The rate of retraction accelerated during the first 2 months of retraction. Molar anchor loss of approximately 0.6 mm occurred in the study group, and 1.8 mm occurred in the control group during the 4 months. Conclusion: The rate of retraction with study group was twice as faster when compared to the control group, accelerating during the first 2 months of retraction. There was better anchorage control with the undecorticated molar segment during the retraction period but was found to increase as time advanced.